Predicting a process window for the roll-to-roll deposition of solvent-engineered SnO2 in perovskite solar cells. Issue 23 (13th October 2022) - Richards, David; Burkitt, Daniel; Patidar, Rahul; Beynon, David; Watson, Trystan
Abstract : We use a coating model to enable homogenous deposition of SnO2 for perovskite solar cells. Solvent engineering of the formulation and adaptation of coating parameters is used to apply defect free layers using slot-die coating. Abstract : Lightweight flexible perovskite solar cells (PSCs) offer advantages over rigid solar cells including power to weight, variety of form factor and ability to scale. With breakthroughs in the power conversion efficiency (PCE) of PSCs, scaling up PSCs with similar performance has become a topic of interest. Roll-to-roll (R2R) manufacturing is one promising method to leverage the low temperature processing ability of PSCs. In this work, we demonstrate the R2R slot-die coating of the SnO2 electron transport layer, applying the low flow limit to showcase its pertinence in assessing the coating window for slot-die coating. It was observed that low flow limit can accurately predict the processing window for solvent-engineered SnO2 solutions streamlining scale up from benchtop to full R2R coating. We achieved a PCE of 16.35% for R2R-coated SnO2 -based MAPbI3 perovskite devices exceeding the performance of benchtop-coated devices.